Customer Experience Management and Brand Loyalty: The Mediating Role of Customer Satisfaction of Nigerian Telecommunication Firms in Port Harcourt (Texas Journal of Multidisciplinary Studies, 2024)
This empirical investigation questions the intersection of Customer Experience and Customer Loyalty to the operations of the service market segment. Anonymous questionnaire was distributed to 248 participants, chosen among organizations that operate in the sphere of customer loyalty service, thus, the empirical sample was created. The type of analytical approach taken involved the use of Partial Least Squares (PLS) in Design Structural Equation Modeling (SEM). The hierarchical framework as defined by the emerged framework comprises three specific dimensions, which are customer experience, entailing the core service quality, price transparency mechanisms and brand image perception. These elements have significant impact on customer loyalty measures. The empirical results confirm that the positive experience of the customers is a positive contributor to customer loyalty. The findings of the study contain important implications to the maintenance and management of relationship with clients in service businesses, providing the strategic best practice of maintaining loyalty through personalized and tailored engagement processes. Providing customers with outstanding experiences and interactions that are critical in ensuring success of the organization, maintaining competitive edge within the service industry remains key to brand loyalty. In addition, this study attempts to advance the knowledge of the marketing practitioners towards the identification of the exact mechanisms that customer experiences can build and its subsequent impact on loyalty behaviors. As a result, organizations gain the insights to strategically influence and control brand loyalty using the proxies of this study to improve interactions with the clients and deepen customer relationships.